Dissemination of newly emerged polymyxin B sensitiveVibrio choleraeO1 containing Haitian‐like genetic traits in different parts of India. Issue 9 (September 2018) - Samanta, Prosenjit; Saha, Rudra Narayan; Chowdhury, Goutam; Naha, Arindam; Sarkar, Sounak; Dutta, Shanta; Nandy, Ranjan Kumar; Okamoto, Keinosuke; Mukhopadhyay, Asish Kumar
Abstract : Purpose. : Two natural epidemic biotypes of Vibrio cholerae O1, classical and El Tor, exhibit different patterns of sensitivity against the antimicrobial peptide polymyxin B. This difference in sensitivity has been one of the major markers in biotype classification system for several decades. A recent report regarding the emergence of polymyxin B‐sensitive El Tor V. cholerae O1 in Kolkata has motivated us to track the spread of the strains containing this important trait, along with Haitian‐like genetic content, in different parts of India. Methodology. : We have collected 260 clinical V. cholerae O1 strains from 12 states in India and screened them for polymyxin B susceptibility. Genetic characterization was also performed to study the tcpA, ctxB and rtxA genotypes by allele‐specific polymerase chain reaction (PCR) and nucleotide sequencing. Results. : Interestingly, 88.85 % of the isolates were found to be sensitive to polymyxin B. All of the states, with the exception of Assam, had polymyxin B‐sensitive V. cholerae strains and complete replacement with this strain was found in eight of the states. However, from 2016 onwards, all the strains tested showed sensitivity to polymyxin B. Allele‐specific PCR and sequencing confirmed that all strains possessed Haitian‐like genetic traits. Conclusion. : Polymyxin B‐sensitive strains have begun to spread throughout India and may lead to the revision of the biotype classification. The dissemination of these new variant strains needs to be carefully monitored in different endemic populations through active holistic surveillance to understand their clinical and epidemiological consequences.